Zur Doppelbödigkeit des Unterrichts als Bühne Eine rekonstruktive Fallanalyse zur Untersuchung der Interaktionsordnung des Unterrichts - Reischl, Julia (Schriftenreihe der DGfE-Kommission Psychoanalytische Pädagogik, 2023)
Which practices and dynamics can be identified in the interaction between teachers and students? How is the interactional order of teaching established and maintained? What insights can the documentary method and depth hermeneutics provide and what added value does method triangulation offer? The study investigates the interaction in a 3rd grade of lower secondary school over a survey period of two school years.